(untitled) (Experimental biology, 2026)
Interferons are signaling proteins secreted by the cells of birds and mammals in response to viral infection, which activates nonspecific antiviral immune response. In recent years, interferon preparations have shown effective in the prevention and treatment of viral infections in humans and animals. However, such preparations are not produced in Kazakhstan and are supplied from other countries. Therefore, developing a local technology for producing recombinant interferons for farm animals is an important task for strengthening Kazakhstan’s veterinary security. In this study, the α-interferon gene of a cattle (Bos taurus) was cloned and a recombinant protein producer based on the bacterium Escherichia coli was developed. In addition, optimal cultivation conditions to produce recombinant protein were selected. However, it was determined that the protein produced accumulated in inclusion bodies and was not able to be isolated under native conditions. Accordingly, the synthesized recombinant protein was isolated after dissolution in a buffer containing 6 M guanidine chloride and then purified and refolded using metal affinity chromatography with Ni-NTA agarose. Finally, the yield of the target protein after refolding was 3.3 mg per liter of bacterial culture. Thus, a laboratory method for producing bovine recombinant α-interferon was developed. In the future, it is planned to conduct tests of the antiviral activity of the recombinant protein and scale up the technology for industrial production of the domestic drug.